Penanaman Pohon Flamboyan dan Tabebuya untuk Meningkatkan Estetika dan Kualitas Lingkungan di Desa Peron melalui Program Agrosiaga PPK ORMAWA HIMA IPA dan Lingkungan - Haris, Amnan; Naufal, Muhammad Agnaf; Oktaviana, Maria Nafraim; Wulandari, Suci; Pradama, Daffa Evan; Revalina, Aurelia Dias Nanda; Primagati, Aira Trismadya; Rozan, Ajmal; Najwa, Rizqa; Rahmawati, Maisya; Setiyanda, Karista Gadis; Sakti, Bernov Lakhomi Pujangga; Hidayat, Farid Nur; Putri, Ade Anggun Wana; Rahmawati, Umi; Hermawati, Erna (Informa Science, 2025)
Peron Village, located in Limbangan Subdistrict, Kendal Regency, lies on the western slopes of Mount Ungaran and forms part of the Bodri Watershed (DAS Bodri), one of the priority watersheds in Central Java. The village has developed an agroforestry system integrating coffee, sugar palm, and rice fields; however, as an upstream area, the land faces severe ecological pressures in the form of high soil erosion. This erosion threatens to reduce land productivity and increase the risk of flooding in downstream regions. A strategic intervention undertaken is the planting of flamboyant trees (D. regia) and tabebuya trees (T. rosea) as protective and shade vegetation. Both species possess strong root systems and dense canopies, making them effective in reducing erosion rates, enhancing water infiltration, and enriching the aesthetic value of the village landscape. Beyond their ecological functions, flamboyant and tabebuya trees also contribute to the community’s socio-cultural well-being by creating green spaces that foster comfort and strengthen the identity of the agroforestry landscape. Thus, the planting of flamboyant and tabebuya trees in Peron Village serves not only as a measure to mitigate erosion and flooding but also as an integrative strategy for sustaining ecological balance, economic resilience, and social cohesion in the buffer zone of the Bodri Watershed. Keywords: Bodri Watershed; Agroforestry; Flood Mitigation; Upstream Greening; Landscape Aesthetics